Serum estradiol levels in controlled ovarian stimulation directly affect the endometrium. (August 2017) - Ullah, Kamran; Rahman, Tanzil Ur; Pan, Hai-Tao; Guo, Meng-Xi; Dong, Xin-Yan; Liu, Juan; Jin, Lu-Yang; Cheng, Yi; Ke, Zhang-Hong; Ren, Jun; Lin, Xian-Hua; Qiu, Xiao-Xiao; et al.
Abstract : Previous studies have shown that increasing estradiol concentrations had a toxic effect on the embryo and were deleterious to embryo adhesion. In this study, we evaluated the physiological impact of estradiol concentrations on endometrial cells to reveal that serum estradiol levels probably targeted the endometrium in controlled ovarian hyperstimulation (COH) protocols. An attachment model of human choriocarcinoma (JAr) cell spheroids to receptive-phase endometrial epithelial cells and Ishikawa cells treated with different estradiol (10 −9  M or 10 −7  M) concentrations was developed. Differentially expressed protein profiling of the Ishikawa cells was performed by proteomic analysis. Estradiol at 10 −7  M demonstrated a high attachment rate of JAr spheroids to the endometrial cell monolayers. Using iTRAQ coupled with LC–MS/MS, we identified 45 differentially expressed proteins containing 43 significantly upregulated and 2 downregulated proteins in Ishikawa cells treated with 10 −7  M estradiol. Differential expression of C3, plasminogen and kininogen-1 by Western blot confirmed the proteomic results. C3, plasminogen and kininogen-1 localization in human receptive endometrial luminal epithelium highlighted the key proteins as possible targets for endometrial receptivity and interception. Ingenuity pathway analysis of differentially expressed proteins exhibited a variety of signaling pathways, including LXR/RXR activation pathway and acute-phase response signaling and upstream regulators (TNF, IL6, Hmgn3 and miR-140-3p) associated with endometrial receptivity. The observed estrogenic effect on differential proteome dynamics in Ishikawa cells indicates that the human endometrium is the probable target for serum estradiol levels in COH cycles. The findings are also important for future functional studies with the identified proteins that may influence embryo implantation.